INSTRUMEN PEMBIAYAAN BERKELANJUTAN DAN PERAN PERBANKAN SYARIAH DALAM PEMBIAYAAN BERKELANJUTAN - Nur Hasanah Azizah; Ashari Seribu Dinar; Heni Noviarita (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2026)
Global environmental pressures that disrupt social and economic stability demand a financial system grounded in sustainability. Islamic banking holds a strategic position in implementing sustainable financing, as the principles of justice (al-‘adl), public interest (al-maslahah), and environmental preservation (hifz al-bi’ah) align with sustainability objectives. This study employs a descriptive approach through literature review using secondary data derived from journals, reports, and financial policies. The findings indicate that green financing practices through murabahah, musharakah, ijarah, and green sukuk contracts have encouraged environmentally friendly financing, although challenges remain due to low literacy, regulatory uncertainty, and limited innovation in green financial products. Nevertheless, Islamic finance holds significant potential to strengthen the national green finance ecosystem by channeling funds ethically, equitably, and in an environmentally responsible manner.